If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -8) + -13 = 5 Reorder the terms: 9(-8 + x) + -13 = 5 (-8 * 9 + x * 9) + -13 = 5 (-72 + 9x) + -13 = 5 Reorder the terms: -72 + -13 + 9x = 5 Combine like terms: -72 + -13 = -85 -85 + 9x = 5 Solving -85 + 9x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '85' to each side of the equation. -85 + 85 + 9x = 5 + 85 Combine like terms: -85 + 85 = 0 0 + 9x = 5 + 85 9x = 5 + 85 Combine like terms: 5 + 85 = 90 9x = 90 Divide each side by '9'. x = 10 Simplifying x = 10
| 8x-64=8 | | 2/4n=6 | | 2(1x+4)-1=15 | | Vout=Vs(P*0.018+0.5) | | 5x=-2x+25 | | 55+(4x-5)=x | | (x-598)=0 | | 4x-18=3x+9 | | 7x+21=91 | | 116-31=x | | 5x+0.5y+1z=100 | | 3/35-8 | | 35/3-8 | | 3(9-6x)-10x=1 | | 12(y+89)= | | 10x-118=2x-6 | | 75+75=x | | 4u-7=-35 | | 6-x^2=-39 | | 124+37=x | | 27x^7/9x^2 | | x+(12)=8 | | 60+63=x | | n*1270=375 | | 4x-13=5x+8 | | 40+(5x+14)=x | | 9j+12k-3p=0 | | y^-9/y^-6 | | -2t^3+12t^2+32t=0 | | x+252=3x | | 24n=13m+19 | | 4(9+3x)-12=16 |